Information carried by a surface-plasmon-polariton wave across a gap - Agrahari R.; Lakhtakia A.; Jain P.K. (My University, 2025)
Faster communication between electronic devices inside a semiconductor chip may be enabled by optical interconnects based on surface-plasmon-polariton (SPP) waves, as their high localization overcomes the size mismatch between optical and electronic devices. Hence, we solved the Maxwell equations in the time domain to investigate the jump of a pulse-modulated carrier SPP wave across a semi-infinite gap on the metallic side of a planar metal/dielectric interface. The Drude model was used for the susceptibility of the metal and the air was taken as the dielectric material in our calculations. The Pearson correlation coefficient of the appropriate component of the Poynting vector at two points on either side of the gap was calculated. After an abrupt termination of the metal, reflection was very low and the signal continued to propagate in air as a precursor followed by a somewhat distorted version of the launched pulse. Information encoded as the existence of a pulse was found to be strongly and positively correlated with the transmitted signal. When the metal/air interface was restored after a gap of width equal to the carrier wavelength in free space, the signal received across the gap still comprised a precursor and a main pulse that were still strongly and positively correlated with the transmitted signal. Thus, information continued to propagate in the forward direction for a long distance after the gap, a promising result for SPP-wave-based optical interconnects. © 2018 Author(s).